THE INFLUENCE OF SPIRITUAL LEADERSHIP ON AFFECTIVE COMMITMENT THROUGH CALLING AND MEMBERSHIP (A STUDY AT ZAINAB MOTHER AND CHILD HOSPITAL IN PEKANBARU) - Nageeta Tara Rosa; Djamaludin Ancok (Universitas Gadjah Mada, 2020)
This current research examines the influence of spiritual leadership in affective commitment through calling and membership. This research uses a sample of 110 employees either interact or experience direct policies toward the leader with a minimum of 2 years working period at Zainab Mother and Child Hospital in Pekanbaru, Riau Province. Simple and Multiple Linear Regression is used in this study to measure the contribution toward the dependent variable by using the IBM SPSS version 20. The analysis then shows the results that spiritual leadership has a significant effect on calling and membership. Calling significantly influences affective commitment, and it is similar to membership, which has significant value relates to affective commitment. Recommendations for leaders, employees, and future research are discussed.